Interdisciplinary handbook of trauma and culture - Ataria, Yochai; Gurevitz, David; Pedaya, Haviva; Neria, Yuval (Springer, 2016)
This lofty volume analyzes a circular cultural relationship; it not only explores how trauma is reflected in cultural processes and products, but also how trauma itself can shape literature, visual and performing arts, architecture, religion, and mythmaking. Analyses of American, Israeli, and Japanese art forms reveal the power of trauma, as reflected in varying roles of perpetrator, victim, and witness. Traumatic complexities are traced through the consideration of spirituality, religion, movement, philosophy, psychology, and trauma theory. Additionally, essays on authors such as Kafka, Plath, and Cormac McCarthy examine how narrative can blur the boundaries of personal and collective experience. Among the topics covered: Television: a traumatic culture. From Hiroshima to Fukushima: comics and animation as subversive agents of memory in Japan The difference between trauma and fear The death of the witness in the era of testimony: Primo Levi and Georges Perec. Sigmund Freud Moses and Monotheism and the possibility of writing a traumatic history of religion. Placing collective trauma within its social context: the case of the 9/11 attacks. Killing the killer: rampage and gun rights as a syndrome. This volume appeals to multiple readerships including researchers and clinicians, sociologists, anthropologists, historians, and media researchers.